A rapid alkyl homologue distribution analysis of ionic surfactants by two-dimensional HPLC - HORIGUCHI, Yasunobu; MATSUTANI, Shigeaki; TANAKA, Shoichi; HOBO, Toshiyuki; NOGUCHI, Hideo (BUNSEKI KAGAKU, 1998)
An alkyl homologue distribution analysis of surfactants contained in household detergents or toiletries involved intricate work. A rapid analysis method using a two-dimensional (2D) HPLC has been developed. In the case of anionic surfactants, each surfactant, such as carboxylates or sulfates, is separated from matrices according to the type of anionic group by an anion exchange column (1D), and eluted as a single peak. The eluted surfactant is trapped on a C8 short column and then transferred to a C18 analysis column (2D) by a switching technique. The alkyl homologs can be analyzed in this a time of less than 40 min. In the case of cationic or amphoteric surfactants, a cation exchange column was used as an 1D column. The method was successfully applied for the analysis of carboxylates, sulfates, sulfonates, quaternary ammonium salts, alkyl pyridinium salts, amidobetains, and other surfactants in household formulations.